2016
DOI: 10.1088/1361-6420/33/1/015003
|View full text |Cite
|
Sign up to set email alerts
|

Uniform Penalty inversion of two-dimensional NMR relaxation data

Abstract: The inversion of two-dimensional NMR data is an ill-posed problem related to the numerical computation of the inverse Laplace transform. In this paper we present the 2DUPEN algorithm that extends the Uniform Penalty (UPEN) algorithm [Borgia, Brown, Fantazzini, Journal of Magnetic Resonance, 1998] to two-dimensional data. The UPEN algorithm, defined for the inversion of one-dimensional NMR relaxation data, uses Tikhonov-like regularization and optionally non-negativity constraints in order to implement locally … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
55
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 26 publications
0
55
0
Order By: Relevance
“…26 Basser et al 8 implemented L 1 -penalized relaxometry in the context of the development of a marginal distribution constrained optimization (MADCO) method for constrained reconstruction of 2D relaxometry distributions. Samples were obtained from an arthroplasty procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…26 Basser et al 8 implemented L 1 -penalized relaxometry in the context of the development of a marginal distribution constrained optimization (MADCO) method for constrained reconstruction of 2D relaxometry distributions. Samples were obtained from an arthroplasty procedure.…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to tissue breakdown within the osteoarthritic cartilage relaxometry. 26 Basser et al 8 implemented L 1 -penalized relaxometry in the context of the development of a marginal distribution constrained optimization (MADCO) method for constrained reconstruction of 2D relaxometry distributions. While commenting that this penalty is likely to be more applicable to the sparse solution matrices obtained in a typical experiment, comparison of penalties was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…To maximize the amount of information that can be extracted from LF‐NMR signal generation, we adapted and used a PDCO solver with excellent reconstruction accuracy that outperformed other in‐house NMR instrument's mathematical reconstruction programs (Wiesman et al, ). Signal reconstruction is essentially an ill‐posed ILT problem (Bortolotti et al, ; Reci et al, ); this implies that similar relaxation curves and noise in the measurements can result in very different reconstruction spectra and/or a high signal‐to‐noise ratio (SNR). In previous reports (Berman et al, ; Campisi‐Pinto et al, ; Wiesman et al, ), it was demonstrated that if an l 2 regularization term is added to the objective function of a common regularization, as seen in Eq.…”
Section: Methodsmentioning
confidence: 99%
“…NMR signal reconstruction is an ill‐posed inverse Laplace transform (ILT) problem . Therefore, very similar energy relaxation time curves and/or a relatively low noise level in the measurements can result in very different reconstructed spectra and/or signal to noise ratio (SNR).…”
Section: Methodsmentioning
confidence: 99%